MANAJEMEN ASUHAN KEBIDANAN BAYI BARU LAHIR NY ‘S’ DENGAN BCB/SMK/SPONTAN DI PUSKESMAS TINGGIMONCONG KABUPATEN GOWA - Sumaifa, Sumaifa; Nurfadila, Nurfadila; Ibrahim, Sitti Hasrah (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2025)
Physiological newborns are babies born with a gestational age of more than or equal to 37 weeks with a weight of 2500 grams to 4000 grams. During birth, many physical and psychological changes begin to occur in the baby's body, therefore careful supervision is needed to determine how to adapt to life outside the womb. Newborns really need immediate, fast, precise, safe and clean care. This is important for newborns Research Objective: The case study is to implement Normal Newborn Midwifery Care for Baby Mrs. S at the Tinggimoncong Health Center in 2024 with the implementation of midwifery care management according to the midwife's authority. Research Method: The method used in this study is descriptive with a case study approach using seven steps of Varney midwifery care management and SOAP progress notes. Results of the case study research have been carried out through the assessment and analysis of data on Midwifery Care for Newborns Mrs. "S". with BCB / SMK / Spontan at the Tinggimoncong Health Center, Gowa Regency. .Conclusion: The conclusion obtained from the case study of Mrs. S, a normal newborn baby at Tinggimoncong Health Center, is that the care that has been given was successful, marked by the baby's general condition being good, the baby did not experience metabolic disorders, the baby was able to adapt to life outside the womb, the baby had been breastfed, there was no umbilical cord infection and vital signs were within normal limits, heart rate: 136 x / minute, temperature: 36.6 oC, breathing: 48x / minute. Suggestion: It is recommended that mothers always carry out umbilical cord care to prevent umbilical cord infection and are expected to check their babies at health service facilities if there are abnormalities in the baby and provide immunizations according to schedule and can follow the suggestions given by health workers. Midwives must improve their abilities in implementing newborn cases in general and especially in normal newborns. It is expected that in providing care to clients, midwifery management and documentation of care must be implemented as a responsibility if there is a lawsuit